Physics of ultra cold atoms and their applications : Miniature quantum frequency standard based on the phenomenon of coherent population trapping in vapours of 87Rb atoms. (11th June 2020) - Skvortsov, M N; Ignatovich, S M; Vishnyakov, V I; Kvashnin, N L; Mesenzova, I S; Brazhnikov, D V; Vasil'ev, V A; Taichenachev, A V; Yudin, V I; Bagayev, S N; Blinov, I Yu; Pal'chikov, V G; et al.
Abstract: We report the results of the development and production of a quantum frequency standard (QFS) based on the coherent population trapping (CPT) resonance observed on the D1 absorption line of 87 Rb atoms. The effect of various physical factors on the QFS frequency is studied, and the optimal physical parameters of the device to attain the best frequency stability are determined. The measured relative frequency instability (Allan deviation) is ≈9 × 10 -12 for the averaging time of 1 s, 3 × 10 -13 for 1000 s, and 1.5 × 10 -12 for 24 hours. For a volume of 60 cm 3, the power consumption of the entire device is 300 mW. The designed QFS can be used in a new-generation satellite navigation systems with increased accuracy and reliability, as well as for solving a number of other problems of science and technology